2007
DOI: 10.1002/ptr.2168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidative properties of Allium species growing wild in Italy

Abstract: The genus Allium (Alliaceae) is an important dietary source of antioxidant phytochemical products. The antioxidant activity of some Allium species is well known but no information is available on the in vitro antioxidant activities of Italian Allium species growing wild. The aim of this study was to examine the in vitro antioxidant activity of aqueous extracts of different parts belonging to three Allium species growing wild, endemic to Italian flora: Allium neapolitanum Cyr., Allium subhirsutum L. and Allium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 27 publications
(25 reference statements)
10
52
1
1
Order By: Relevance
“…in 'Roztocze' ecotype, respectively. Nencini et al [25] reported that polyphenol content in leaves of three Allium species growing wild in Italy and two clones of Allium sativum L. ranged from 0.41 mg of GAE/g fresh weight to 0.59 mg of GAE/g fresh weight and was generally directly correlated with the antioxidant/antiradical activity. In our study we did not show this correlation.…”
Section: Mineral Compounds Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…in 'Roztocze' ecotype, respectively. Nencini et al [25] reported that polyphenol content in leaves of three Allium species growing wild in Italy and two clones of Allium sativum L. ranged from 0.41 mg of GAE/g fresh weight to 0.59 mg of GAE/g fresh weight and was generally directly correlated with the antioxidant/antiradical activity. In our study we did not show this correlation.…”
Section: Mineral Compounds Contentmentioning
confidence: 99%
“…Gorinstein et al [14] reported that the percentage of scavenged of free radicals for fresh cloves was 68.9 %. Nencini et al [25] reported that leaves of tested clones of Allium sativum seem to have higher antioxidant capability than the bulbs, and what is more garlic exhibited very low antioxidant power in comparison with species growing wild.…”
Section: Mineral Compounds Contentmentioning
confidence: 99%
“…Furthermore, the antioxidative properties of the aqueous extracts of bulbs, bulblets, leaves and flowers of A. neapolitanum were investigated showing a good antiradical power 9 . It was also showed that the good antihypertensive effects of the aqueous extract of bulbs of A. neapolitanum could to be associated to interactions with adrenergic receptor β 2 antagonist, involved in blood pressure regulation 10 .…”
Section: Thementioning
confidence: 99%
“…In a study to evaluate the antioxidant potential of wild Allium species (A. neapolitanum, A. roseum, A. subhirsutum and A. sativum) growing in Italy, Nencini and colleagues report significantly higher levels of antioxidant activity as measured by FRAP test and a DPPH assay in the flowers or leaves, with lowest antioxidant capacity consistently reported for the bulbs [121].…”
Section: Tissue Type and Developmental Stagementioning
confidence: 99%